ERP-Mediated Information Integration: An Empirical Case Study on Supply Chain Efficiency in Morocco’s Red Meat Sector - BENTALEB , Fatima Zahra; TAKI , Mounaim (Revue Internationale des Sciences de Gestion, 2023)
In the framework of the Generation Green Strategy (2020-2030) and the preceding Green Morocco Plan (2008-2020), the red meat industry is recognized as a substantial catalyst for food security, employment, and the promotion of modernization through the adoption of technological advancements. The primary aim of this research paper is to examine the extent to which information integration, facilitated through ERP implementation, affects the supply chain performance of agri-food companies. To this end, the article examines a case study of an agri-food holding that successfully implemented a customized ERP system in 2016. Employing a qualitative research strategy, twelve semi-structured interviews were conducted across the six enterprises within the holding until theoretical saturation was reached. The investigation’s findings demonstrate the substantial impact of ERP-mediated information integration on supply chain performance, leading to improvements in decision-making processes and operational efficiency. This study serves as a basis for further academic investigations and policy discussions in the pursuit of an effective, sustainable, and technologically advanced agri-food supply chain. Furthermore, it suggests the need for additional research in order to get a thorough comprehension of the complex effects of ERP systems on the dynamics of agri-food supply chains.